The Role of New Media in Facilitating Entrepreneurship in Tourism - Case Study: Promoting Komodo Island in East Nusa Tenggara - Dessy Kania (Universitas Multimedia Nusantara, 2010)
Tourism is an important component of the Indonesian economy as well as a significant source of the country's foreign exchange revenues. According to the Center of Data and Information - Ministry of Culture and Tourism, the growth of foreign visitor arrivals to Indonesia has increased rapidly by 9.61 percent since 2010 to the present. One of the most potential tourism destinations is Komodo Island located in East Nusa Tenggara. With the island's unique qualities, which include the habitat of the Komodo dragons and beautiful and exotic marine life, it is likely to be one of the promising tourism destinations in Indonesia and in the world. In 1986, the island has been declared as a World Heritage Site by UNESCO. The Ministry of Culture and Tourism continuously promotes many of the country's natural potential in tourism through various media: printed media, television and especially new media. However, there are challenges for the Indonesian tourism industry in facilitating entrepreneurship skills among the local people in East Nusa Tenggara. According to the Central Bureau of Statistics (2011), East Nusa Tenggara is considered as one of the poorest provinces in Indonesia where the economy is lower than the average, with a high inflation of 15%, and unemployment of 30%. This research is needed to explore further the phenomenon behind the above facts, aiming at examining the role of new media in facilitating entrepreneurship in the tourism industry in Komodo Island. The results of this study are expected to provide insights that can help local tourism in East Nusa Tenggara. Keywords: Tourism, Entrepreneurship, New Media